Shift of the western boundary of the distribution area of Micromeria cristata (Hampe) Griseb. and Steptorhamphus tuberosus (Jacq.) Grossh. - Petrovic, Danka; Stesevic, Danijela (Acta Botanica Croatica, 2011)
During field investigations of Mt Rumija, two new taxa for the flora of Montenegro were recorded: Micromeria cristata (Hampe) Griseb. and Steptorhamphus tuberosus (Jacq.) Grossh. From the phytogeographic point of view these data indicate a change in the distribution area of both taxa, which have shifted to the west. Ashort overview of the taxonomic treatment of both genera is given.